1996
DOI: 10.17016/feds.1996.39
|View full text |Cite
|
Sign up to set email alerts
|

Long-Horizon Exchange Rate Predictability?

Abstract: Several authors have recently investigated the predictability of exchange rates by fitting a sequence of long-horizon error-correction regressions. We show that in small to medium samples such a procedure gives rise to spurious evidence of predictive power. A simulation study demonstrates that even when using this technique on two independent series, estimates and diagnostic statistics suggest a high degree of predictability of the dependent variable. We apply a simple modification of the long-horizon regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, studies by Mark (1995), Chinn and Meese (1995), MacDonald and Taylor (1994) have shown that for a small set of monetary fundamentals, the out-of-sample forecast improves upon the random walk model. The robustness of these results has been questioned by Berben and van Dijk (1998) and Berkowitz and Giorgianni (2001) based on the assumption of a stable cointegrating relationship. Recent studies admit the possibility albeit difficulty in beating the random walk forecast (see for example, Mark and Sul, 2001; Rapach and Wohar, 2002).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…However, studies by Mark (1995), Chinn and Meese (1995), MacDonald and Taylor (1994) have shown that for a small set of monetary fundamentals, the out-of-sample forecast improves upon the random walk model. The robustness of these results has been questioned by Berben and van Dijk (1998) and Berkowitz and Giorgianni (2001) based on the assumption of a stable cointegrating relationship. Recent studies admit the possibility albeit difficulty in beating the random walk forecast (see for example, Mark and Sul, 2001; Rapach and Wohar, 2002).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The theoretical foundations for spurious regression bias with stationary but close to unit root regressors is provided by Phillips (1986Phillips ( ), (1998, Marmol (1998), Tsay and Chung (2000), Granger, Hyung, and Jeon (2001), and Jansson and Moreira (2006). Spurious regression bias is also observed in models for stock returns using dummy variables as the predictors (see Powell, Shi, Smith, and Whaley (2006)), in error-correction regressions (see Berkowitz and Giorgianni (1996)) and in predictive models for the variance of stock returns (see Paye (2006)). Phillips (2001) studies problems using bootstrap methods in the presence of spurious regressions.…”
Section: Spurious Regression and Data Miningmentioning
confidence: 99%
“…First, I show that with exogenous regressors, the scaled standard t-statistic will be normally distributed and standard inference can thus be performed. Second, when the regressors are endogenous, the inferential methods can be suitably modified to correct for the biasing endogeneity effects; this can be seen as an analogue of the inferential procedures developed by Campbell and Yogo (2006) for short-run, 1-period-horizon 1 Other applications of long-horizon regressions include tests of exchange rate predictability (Mark (1995), Berkowitz and Giorgianni (2001), and Rossi (2005)), the Fisher effect (Mishkin (1990(Mishkin ( ), (1992, Boudoukh and Richardson (1993)), and the neutrality of money (Fisher and Seater (1993)).…”
Section: Introductionmentioning
confidence: 99%